EARLY CHECKING OF GENETIC STABILITY OF CORK OAK SOMATIC EMBRYOS BY AFLP ANALYSIS. - Hornero, J; Martinez, I; CELESTINO, C; Gallego, F J; Torres, V; TORIBIO, M (International Journal of Plant Sciences, 2001)
Early checking of the genetic stability, of tissue culture-derived plants is necessary to obtain all the potential benefits of clonal forestry. Previous work in Quercus suber L. using random amplified polymorphic DNA (RAPD) markers showed no genetic variation among somatic embryos within embryogenic lines of zygotic origin. Genetic fingerprinting based on amplified fragment length polymorphisms (AFLP) allows the direct analysis of variation at the entire DNA level by generating more reproducible markers than RAPDs. To confirm the absence of genetic variation within six embryogenic lines of zygotic origin, six primer pairs were selected out of 48 combinations of primers for revealing up to 512 AFLP markers, 301 of them (58.8%) being polymorphic. The mean number of markers per genotype was 375. Again differences were recorded among embryogenic lines, even between those that arose from half-sib zygotic embryos, but no variation was observed among somatic embryos within embryogenic lines. To check variation in embryogenic lines raised from non-embryonic tissues, somatic embryogenesis was induced in expanding leaves collected from sprouts originating in three mature cork oak. DNA was extracted from leaves and from somatic embryos derived from each tree, and three primer pairs showed 165, 110, and 108 markers per genotype/tree, respectively. In one tree, AFLP patterns generated from leaves and somatic embryos were identical, but variation was detected in samples from the other two trees. Although the level of genetic variation detected in these lines (5.6% and 7.3% of polymorphism, respectively) is lower than that recorded for half sibs of cork oak (25%–31%), its influence on phenotypic variation needs further assessment. [ABSTRACT FROM AUTHOR]
Keywords: AFLP; Cork oak; DNA markers; in vitro culture; Quercus suber; somaclonal variation; Somatic embryogenesis

Testing the conservation of Quercus spp. microsatellites in the cork oak, Q-suber L. - Hornero, J; Gallego, F J; Martinez, I; TORIBIO, M (SILVAE GENETICA, 2001)
The transferability of microsatellite (SSR) loci from Quercus spp. to cork oak (Quercus suber L.) was investigated. Semi-automated analysis of fluorescently-labelled PCR fragments was used to test 24 primer sets developed for Q. myrsinifolia BLUME, Q. petraea (MAT7.) LIEB. and Q. robur L. in 41 cork oak trees from four stands covering the main area of distribution of the species in Spain. Successful cross-species events occurred for 13 loci (54%). Two of them were monomorphic and another two appeared as multilocus. High levels of genetic variability were detected both for the number of alleles, 62 (7.5 per polymorphic locus, with a maximum number of 19 in locus ssrQpZAG110) and for the expected heterozygosity (mean H-E = 0.648). These results were much higher than those previously reported by other authors using allozyme loci. The usefulness of the. SSR loci successfully amplified for studies on population genetics of cork oak is discussed.
Keywords: Cork oak; Fagaceae; microsatellites; Quercus suber

Testing somaclonal variation using RAPDs in Quercus suber L. somatic embryos. - Gallego, F J; Martinez, I (International Journal of Plant Sciences, 1997)
Focuses on the use of Random Amplified Polymorphic Deoxyribose nucleic acid (RAPD) profiles to test somaclonal variation in Quercus suber L. somatic embryous during recurrent embryogenesis. Number of primers used to amplify DNA from isolated embryos; Use of somatic embryogenesis from immature zygotic embryos; How somaclonal variation was detected.
Keywords: Cork oak; SOMATIC embryogenesis (citation)